Microalgae-based carbohydrates: A green innovative source of bioenergy - De Carvalho Silvello, M. A.; Gonçalves, I. S.; Azambuja, S. P. H.; Costa, S. S.; Silva, P. G. P.; Santos, L. O.; Goldbeck, R.
Microalgae contribute significantly to the global carbon cycle through photosynthesis. Given their ability to efficiently convert solar energy and atmospheric carbon dioxide into chemical compounds, such as carbohydrates, and generate oxygen during the process, microalgae represent an excellent and feasible carbohydrate bioresource. Microalgae-based biofuels are technically viable and, delineate a green and innovative field of opportunity for bioenergy exploitation. Microalgal polysaccharides are one of the most versatile groups for biotechnological applications and its content can be increased by manipulating cultivation conditions. Microalgal carbohydrates can be used to produce a variety of biofuels, including bioethanol, biobutanol, biomethane, and biohydrogen. This review provides an overview of microalgal carbohydrates, focusing on their use as feedstock for biofuel production, highlighting the carbohydrate metabolism and approaches for their enhancement. Moreover, biofuels produced from microalgal carbohydrate are showed, in addition to a new bibliometric study of current literature on microalgal carbohydrates and their use.
Keywords: 3G BIOFUEL; METABOLISM; POLYSACCHARIDE; STARCH